Effect of Thallium (I) Ions on the Zinc Electrowinning Process - YUAN, Ning; CHEN, Xi; LIU, Xing; FU, Lin; CUI, Yan; HUANG, Shihong; ZHAO, Wenjia (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The effects of thallium(Ⅰ) ions on the surface morphology, cathode current efficiency, cathode potential, polarization behavior, and electrochemical impedance spectroscopy of zinc electrowinning were studied by scanning electron microscopy and electrochemical measurements. The results showed that with increasing thallium(Ⅰ) ion concentration in the electrolyte, the hydrogen evolution reaction and the galvanic effect produced during zinc electrowinning increased. When the concentration of thallium(Ⅰ) ions in the electrolyte was 0.6 mg L-1, the exchange current density of the zinc electrowinning process was maximum and the polarization was minimum. At this time, the Rct of the equivalent circuit was minimum, the CPE value was minimum, and the charge transfer rate was maximum. The cathodic current efficiency decreased from 80% to 55% when the thallium(Ⅰ) ion concentration was 1.5 mg L-1. The presence of thallium(Ⅰ) ions also affected the surface macro- and microstructure of the zinc deposits. This result confirmed that thallium(Ⅰ) ions have a significant negative influence on the electrowinning of zinc.